2020
DOI: 10.3390/su122410593
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Fear and Crime Prevention Strategy for Sustainability of Safe City

Abstract: Crime is a manifestation of incivility that society attempts to curb, yet faces enormous challenges, as crime is a by-product of urbanization and human advancement. As more agglomeration of the population in cities around the globe, humankind’s safety from being threatened by crime needed to be safeguard to sustain everyday living in cities. Humans’ co-existence with crime and fear of crime in cities vis-a-vis efforts preventing it from occurring has been widely carried out in developed countries. An increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The sense of security in a gated community is formed by the developer's design and the resident community. Lim et al (2020) concluded that the biggest factor influencing security and reducing crime in public spaces is CPTED, rather than CPSD (crime-prevention methods through social development). ; ; ; found that women are more likely to feel insecure than men to do activities in public spaces due to the poor environmental design, such as poor lighting, narrow roads, too many bushes and trees that reduce visibility, and the presence of delinquents and sloppy people.…”
Section: Methodsmentioning
confidence: 99%
“…The sense of security in a gated community is formed by the developer's design and the resident community. Lim et al (2020) concluded that the biggest factor influencing security and reducing crime in public spaces is CPTED, rather than CPSD (crime-prevention methods through social development). ; ; ; found that women are more likely to feel insecure than men to do activities in public spaces due to the poor environmental design, such as poor lighting, narrow roads, too many bushes and trees that reduce visibility, and the presence of delinquents and sloppy people.…”
Section: Methodsmentioning
confidence: 99%
“…Neighbourhood incivilities refer to two types of incivilities, namely: (1) physical incivilities, characterised by observable incivilities (e.g., broken glass, vandalism, and litter), and (2) social incivilities, manifested by disruptive social behaviour (e.g., public drinking and lewd conduct) [42,43], which may also be seen in the physical environment. Neighbourhood incivility encourages residents to allow breaches against social order and be less likely to interfere to deter crime and incivility [44]. Residents thus tend to spend their leisure time at home, and they are unlikely to be in community relationships [45], suggesting low social regulation.…”
Section: Perceived Incivilities and Human-place Bondmentioning
confidence: 99%
“…Enhance safety and security [20,36,37] Promote quality housing [2,38] Optimize emergency response [20,39] Enhance quality of healthcare services through digital technology [40][41][42][43] Encourage urban farming for better living [23,44] Concerning the element of enhancing safety and security, one key initiative in Malaysia is the focus on crime reduction [36,45]. For example, under the safe city initiative through the Ministry of Housing and Local Government, a safer city can be created using several strategies, such as crime prevention through environmental design (CPTED) and crime prevention through social design (CSPD) [46].…”
Section: Smart Living Strategy Referencementioning
confidence: 99%
“…For example, under the safe city initiative through the Ministry of Housing and Local Government, a safer city can be created using several strategies, such as crime prevention through environmental design (CPTED) and crime prevention through social design (CSPD) [46]. With CPTED, information and communication technology (ICT), and mechanical surveillance design initiatives are popular, including the installation of closed-circuit television (CCTV) in public spaces, IoT (internet-of-things) lighting, safety (panic button) alarms, and establishing GIS (geographic information system) mapping for crime detection [36]. In the case of the capital city, Kuala Lumpur, crime is always an important issue for the citizens and the city authorities.…”
Section: Smart Living Strategy Referencementioning
confidence: 99%